PENGARUH EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER), DEBT TO ASSET RATIO (DAR) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA PT. ASTRA AGRO LESTARI Tbk PERIODE 2006-2015 - Ummi Sarliva; Atikah Atikah; Pupu Sopini (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Based on F statiscal test, prove EPS, PER, DAR and ROE simultaneously have the significant effect on the prices of the stock of the sampled PT Astra Agro Lestari Tbk period 2005-2015, but based on the result of the t statistical test, proved that the variable EPS and PER variable partially has significant effect, while the variable DAR and ROE has no effect on the prices of the stock of the sampled PT Astra Agro Lestari Tbk period 2006-2015.Keyword: earning per share, price earning ratio, debt to asset ratio, return on equity